2015
DOI: 10.1186/s12876-015-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

LDP vs ODP for pancreatic adenocarcinoma: a case matched study from a single-institution

Abstract: BackgroundLaparoscopic distal pancreatectomy (LDP) showed advantage of perioperation outcomes for benign and low-grade tumor of the pancreas. The application of LDP for pancreatic ductal adenocarcinoma (PDAC) didn’t gain popular acceptance and the number of LDP for PDAC remains low. We designed a case-matched study to analysis the short- and long-term outcomes of the patients undergoing either Laparoscopic distal pancreatectomy or open distal pancreatectomy for PDAC.MethodFrom 2003 to 2013, 17 patients were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…They also found less blood loss and need for intraoperative transfusion, which was not the case in the present study. Zhang et al in a small case-matched study found also a diminution of the LoS (13 vs. 15.5 days) [7]. On the contrary a retrospective study by Hasselgren et al showed no difference in the LoS but a diminution of blood loss with laparoscopy [19].…”
Section: Discussionmentioning
confidence: 93%
“…They also found less blood loss and need for intraoperative transfusion, which was not the case in the present study. Zhang et al in a small case-matched study found also a diminution of the LoS (13 vs. 15.5 days) [7]. On the contrary a retrospective study by Hasselgren et al showed no difference in the LoS but a diminution of blood loss with laparoscopy [19].…”
Section: Discussionmentioning
confidence: 93%
“…The morbidity in laparoscopic resections are reported as similar to open(2,9) Laparoscopic pancreatic surgery involves a challenging learning curve and literature indicate further studies to recommend it's routine use (2,5,7,9). This case series provide a discussion on laparoscopic pancreatic resections, in a tertiary care center, in view of feasibility and outcome.…”
Section: Introductionmentioning
confidence: 87%
“…Minimal access resection will minimize the incision and provide a better vision during surgery by magnification and zooming (8) with reduced blood loss (2,3,4,5,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several studies reported favorable short-term outcomes like shorter operative times, less postoperative complications, and decreased length of stay (LoS) [7], [8], [9]. A major concern for laparoscopic DP was to maintain oncologic standards for the resection of adenocarcinomas of the body and tail of the pancreas [10], [11].…”
Section: Introductionmentioning
confidence: 99%